2011
DOI: 10.1590/s1415-52732011000400011
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos sobre a relação entre exercício físico, estresse oxidativo e zinco

Abstract: Este trabalho visa a contribuir com informações sobre a relação entre exercício físico, estresse oxidativo e zinco. A formação de espécies reativas de oxigênio durante o exercício pode contribuir para danos tissulares e celulares, prejudicando o desempenho do atleta. Podem amenizar esses efeitos alguns minerais, como o zinco, que atuam como cofator da enzima superóxido dismutase e na regulação da síntese da metalotioneína, proteínas importantes no sistema de defesa antioxidante. No exercício físico, ocorrem di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Furthermore, the increased metabolism may lead to a deficiency of Zn, requiring supplementation in order to maintain normal values and high level performance [ 29 , 30 ]. Furthermore, Andrade and Marreiro [ 31 ] found that during physical exercise, Zn compartmentalization may be impaired, which means that changes in the concentrations of this element may occur in different organic compartments, and this may reflect differences in blood values. However, the mechanisms involved in the metabolism of Zn, as well as its effects in the improvement of physical performance, are not fully understood yet.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increased metabolism may lead to a deficiency of Zn, requiring supplementation in order to maintain normal values and high level performance [ 29 , 30 ]. Furthermore, Andrade and Marreiro [ 31 ] found that during physical exercise, Zn compartmentalization may be impaired, which means that changes in the concentrations of this element may occur in different organic compartments, and this may reflect differences in blood values. However, the mechanisms involved in the metabolism of Zn, as well as its effects in the improvement of physical performance, are not fully understood yet.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of organic trace minerals in the experimental diets possibly led to a higher activation of antioxidant enzymes, such as glutathione peroxidase, inside the eggs, as these enzymes are mineraldependent (Andrade & Marreiro, 2011) and capable of slowing the rates of hydroperoxide decomposition and malonaldehyde production, which are secondary products of oxidation (Ferreira & Matsubara, 1997). Likewise, the active compounds of rosemary (such as carnosol and carnosic acid) are capable of terminating free-radical reactions and scavenging reactive oxygen species (Sánchez-Escalante et al, 2001), preventing the oxidation of yolk fatty acids, as these antioxidant compounds can be transferred from the hen's diet to the egg (Botsoglou et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…This likely results in greater ability to activate antioxidant enzymes in the hen's body, while also enhancing their transfer to the eggs, given that trace minerals are directly involved in the ability to activate those enzymes, including glutathione peroxidase (GSH) by selenium (Se), catalase (CA) by iron (Fe), and superoxide dismutase (SOD) by zinc (Zn), copper (Cu), and manganese (Mn) (Andrade & Marreiro, 2011).…”
Section: Introductionmentioning
confidence: 99%